Integration of groupware characteristics to AIGLE - integrated environment of evolutive software engineering - Braga, Danilo Palácio (2008)
Cooperation reflects a change in the emphasis of the use of the computer to solve problems, migrating from an isolated vision to another that facilitates human interaction. It may be said that the objective of the groupware is to help groups in communication, collaboration and co-ordination of its activities. This research work studies the theoretical aspects of the groupware area and applies them to the prototype of a process-centered software engineering environment, AIGLE - Integrated Environment of Evolutive Software Engineering. The intention was to add functionalities to allow synchronous and asynchronous communication among people co-operating among themselves to achieve a result